KADAR EMISI GAS BUANG PADA SI ENGINE 4 STROKE-LPG FUEL DENGAN VARIASI BUKAAN KATUP GAS - Romandoni, Nanang; Wahyudi, Noorsakti; Faizin, Kholis Nur; Fadillah, Firdho Putra (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
Abstract The use of LPG fuel in spark ignition engines continues to be developed, including the use of converter kits as a conversion tool from gasoline to LPG. However, the use of converter kits is not optimal because the mixture of air and gas has not been mixed heterogeneously in the combustion chamber. Therefore, it is necessary to redesign the converter kits that speed up the mixing process between air and gas. This study aims to evaluate the use of LPG fuel in spark ignition engines with converter kits on variations in throttle valve openings on exhaust gas emissions and exhaust gas temperatures. The research method used is an experiment with variations in the throttle valve opening on the engine are 25%, 50%, 75%, and 100%. Data that will be compared on the use of gasoline and LPG fuels include carbon monoxide (CO), hydrocarbon (HC), and mean gas temperature. The results showed that the use of fuel between gasoline and LPG on exhaust gas emission levels in spark ignition engines with variations in throttle valve openings was able to reduce CO emissions by 92% on average, HC by 72%, and increase the mean average temperature by 17%. This shows that the use of converter kits at each valve opening is able to reduce levels of CO and HC exhaust emissions compared to gasoline. However, it is inversely proportional to the mean gas temperature, at each variation of the gas valve opening there is a significant increase in temperature. This is because the heating value of LPG is greater than that of gasoline.Keywords—Exhaust gas emission, spark ignition engine, throttle valve open